Ответ(ы) на вопрос:
Замена
[latex] log_{5} (x)=y[/latex]
[latex]log_{5} (5x) = 1 + log_{5} (x)=1+y;log^{2}_{5} (5x)=(1+y)^2=y^2+2y+1[/latex]
[latex] log_{5} (25x)=2+ log_{5} (x)=2+y; log^{2}_{5} (25x)=(2+y)^2=y^2+4y+4[/latex]
Подставляем все это в уравнение
[latex]y^2+4y+4-(y^2+2y+1)+y=15[/latex]
[latex]3y+3=15[/latex]
[latex]y= log_{5} (x)=4[/latex]
[latex]x= 5^{4} =625[/latex]
(log(5)x+2)²-(log(5)x+1)²+log(5)x=15
log²(5)x+4log(5)x+4-log²(5)x-2log(5)x-1+log(5)x=15
3log(5)x=12
log(5)x=4
x=625
Не нашли ответ?
Похожие вопросы